Improving Decision Making by Means of a Marketing Decision Support System - van Bruggen, Gerrit H.; Smidts, Ale; Wierenga, Berend (Management Science, 1998)
Marketing decision makers are confronted with an increasing amount of information. This leads to a complex decision environment that may cause decision makers to lapse into using mental-effort-reducing heuristics such as anchoring and adjustment. In an experimental study, we find that the use of a marketing decision support system (MDSS) increases the effectiveness of marketing decision makers. An MDSS is effective because it assists its users in identifying the important decision variables and, subsequently, making better decisions based on those variables. Decision makers using an MDSS are also less susceptible to applying the anchoring and adjustment heuristic and, therefore, show more variation in their decisions in a dynamic environment. Low-analytical decision makers and decision makers operating under low time pressure especially benefit from using an MDSS.